Lunzia austriaca – a bennettitalean microsporangiate structure with Cycadopites-like in situ pollen from the Carnian (Upper Triassic) of Lunz, Austria. Issue 5 (3rd September 2017) - Pott, Christian; Fischer, Thilo; Aschauer, Birgitt
Abstract: Based on new evidence obtained from freshly collected fossils, we here provide an emendation of Lunzia and Lunzia austriaca with an updated interpretation of the organ architecture, function and affiliation. The specimens reveal that Lunzia austriaca is a pollen organ resembling structures assigned to Weltrichia. Lunzia austriaca comprises cup-shaped pollen organs that develop up to about ten, basally fused lobes carrying appendices. The appendices are arranged pairwise and inserted laterally to a rachis-like structure, in a pinnate architecture on their adaxial side and are interpreted as prominent segments or fertile pinnae that bear numerous synangia identifying them as microsporophylls. The nature of the rachis-like structure is not straightforward. The rachis-like structure could either be fused with a bract – this fused structure then constituting the lobes – or itself been modified depicting a foliate appearance. The microsporophylls are narrow at the base and involute apically or with a sterile apical cowl. Numerous synangia with contracted bases are arranged on the inner (adaxial) side of the microsporophylls in long rows. The synangia consist of presumably four pollen sacs (microsporangia), are oblong and dehisce longitudinally. The pollen is monosulcate, elliptical and with a smooth exine (psilate). It is identified as Monocolpopollenites (= Cycadopites ); from the size range, it fits best into Cycadopites accerimus . The architecture and the epidermal anatomy of Lunzia austriaca is discussed and its structure is compared with several contemporary bennettitaleans; sterile foliage and ovulate structures most likely associated with Lunzia austriaca are Pterophyllum filicoides and Westersheimia pramelreuthensis, respectively.